Carbon Footprint Evaluation and Reduction Strategies for a Residential Building in Romania: A Case Study - Alexandru-Mihai BULMEZ; George DRAGOMIR; Sorin Ionuț BOLOCAN; Alin-Ionuț BREZEANU; Mariana FRATU; Nicolae Fani IORDAN; Norbert GOCZ; Răzvan CALOTĂ (My University, 2025)
Single-family residential buildings represent the highest share of building sector in Romania. Their operation emits the most CO2 into Earth’s atmosphere, as most of them are not energy efficient. A life cycle assessment is performed for a case study building, built in 2019 in Romania, establishing its carbon footprint. For this building CO2 emissions are 177.55 tCO2 for the construction stage, 76.19 tCO2 for the operation stage, 3.55 tCO2 for the demolition stage, and a total of 129.76 tCO2 after reducing with the carbon sequestration from vegetation 127.53 tCO2. The main purpose of this study is to analyse the carbon footprint for a typical single-family Romanian household, with an emphasis on the operational stage. The study compares the results and extrapolates them to all single-family residential buildings in Romania regarding CO2 emissions, with an emphasis on the operational stage. The results illustrate a considerable reduction in CO2 emissions from old, high energy consumption buildings to new, low energy consumption buildings. The highest operational stage emissions for old buildings in Romania are 962.94 tCO2 for firewood heating and 573.69 tCO2 for gas boiler heating, as those buildings are not insulated and don’t use a heat pump. Additionally, considering the use of photovoltaic panels for the entire lifespan, the CO2 emissions for the operational stage decrease for the case study building from 76.18 tCO2 to 19.90 tCO2. Moreover, using a heat pump detriments firewood or gas boilers, decreasing CO2 emissions for the operational stage by up to 34% and 26%, respectively. Due to the higher cost of electrical energy compared to natural gas in Romania, gas boilers are more cost-effective than heat pumps. Because of this, and the higher implementation costs, the tendency is towards natural gas. This will in turn result in an increase of CO2 emission for the entire life cycle of the building by approximate 32% for new buildings and 86% for old, high-energy-consumption buildings.